Polygamy between Islamic law, the Iraqi Personal Status Law, and the Kurdistan Region Amendments - Saeed, Nouri Hama (Journal of Legal and Political Studies, 2016)
"The research addressed the subject of the search of polygamy through Islamic jurisprudence and Iraqi Personal Status Law with amendments to the application of article on polygamy by the ‘Kurdistan Regional Parliament’. It started with an introduction included the importance of the subject, being one of the controversial subjects; disputed between the ones who accept polygamy perceiving it as a solution to a large number of family problems and the ones who refuse polygamy and characterize it as an insult or an act of humiliation towards women. The research is divided into four sections: The first section dealt with the concept of marriage and polygamy in Islamic law and Iraqi law. A number of important observations were concluded. The second section established the phenomenon of polygamy at the previous nations, especially among followers of divine religions and the Arabs before Islam, then reported the origin of its legitimacy and the conditions in Islamic law. The third section took up the position of Iraqi Personal Status of polygamy law through the transfer of legal texts. Most of the polygamy references are explained and simplified. Then a number of comments were mentioned considering some of its parts. In addition, amendments were transferred on the application of the law by the Kurdistan Regional Parliament. The research took a number of important notes into consideration in order to hinder the application of the law in a fair and proper way to fit with the legislation of Islamic law. Therefore, a number of suggestions were proposed to the amended law of the Kurdish community to make it more appropriate. The fourth section took a number of facts from the personal status courts in the Kurdistan Region to see how the judges of the amended law work. The actions taken by them to give to those who requested permission to multiculturalism. It concluded with the findings of the most important results as well as recommendations. All the sources were indexed and referenced."
Keywords: Islamic jurisprudence; Iraqi Personal Status Law,humiliation towards women; henomenon of polygamy